Literatura kaszubska w perspektywie antropologii kulturowej - Kuik-Kalinowska, Adela (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2013)
Areas of cultural anthropology studies on example of Kashubian literature indicate the diversity of the issues dealt with in this work. Raising of ethnic consciousness is driven by a strong relationship with the nature, and at the same time influences the perception of what is individual’s and what is common. In the perspective of anthropological research on Kashubian literature artistic representations of the imagination world of Kashubia, which are complementary to the issues of cultural identity in its individual and collective formation. Through the description of the subjects and themes it is possible to bring to light the image of Kashubian cultural reality, its existential, spiritual and social image of Kashubian community life. The Kashubians in the literary image viewable from the anthropological perspective are an ethnic group who speak their own language, nurture their own cultural identity and tradition, and also support a relationship to the past and contemporary European culture.
Keywords: Kashubian literature; cultural anthropology; ethnic awareness; multilingualism